New South African Review 1 : 2010: Development or decline? - Southall, Roger; Pillay, Devan; Naidoo, Prishani; Daniel, John, 1944-2014 (New South African review, 2018)
The publication of the New South African Review produced from the department of sociology at the University of the Witwatersrand, represents the launch of an exciting new annual series of studies in South African politics, economics, and society. Drawing together original contributions, Volume 1 2010 will range widely over South Africa's location in the global economic crisis, the mounting environmental challenges facing the country, and the extent of poverty and unemployment through to the state of Zuma's ANC, land reform, and other critical issues confronting South African society: crime, child trafficking, HIV-Aids, indigent management, the justice system, and so on. Controversial, challenging and critical, the collection is framed by the question of whether South Africa can shift from a present path heralding long-term decline to a more optimistic future of global competitiveness and sustainable development. A vital read for all those wishing to keep track of present policies, trends, and outcomes in South African political economy.